THE EFFECT OF CURRENT RATIO, TOTAL ASSET TURNOVER, DEBT RATIO, AND RETURN ON ASSETS ON PRICE TO BOOK VALUE IN FINANCIAL SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2023–2024 PERIOD - Hanif Fikri Fauzi; Redy Herinanto Albertus; Bonifasia Ekta Fima Natalia; Ilham Tri Murdo (JURNAL ILMIAH EDUNOMIKA, 2026)
The purpose of this study is to examine the effect of the Current Ratio, Total Asset Turnover, Debt to Asset Ratio, and Return on Assets on the Price to Book Value of financial sector companies listed on the Indonesia Stock Exchange during the 2023–2024 period. The method used in this study is a quantitative approach, utilizing secondary data obtained from the financial statements of financial companies listed on the Indonesia Stock Exchange. The sample in this study consists of 25 companies, selected based on the criteria that they are listed on the Indonesia Stock Exchange and have complete financial statements for the research period, namely 2023–2024. The data analysis techniques employed include descriptive statistical analysis, classical assumption tests, and hypothesis testing. The results of the study show that, partially, the Current Ratio has no effect on Price to Book Value, as indicated by the t-value of -3.115 < t-table value of 1.97646. Meanwhile, the Total Asset Turnover variable also has no partial effect on Price to Book Value, as shown by the t-value of -1.336 < t-table value of 1.97646. Similarly, the Debt to Asset Ratio variable does not have a partial effect on Price to Book Value, as indicated by the t-value of -1.269 < t-table value of 1.97646. In addition, the Return on Assets variable also has no partial effect on Price to Book Value, as evidenced by the t-value of -0.332 < t-table value of 1.97646. However, simultaneously, the Current Ratio, Total Asset Turnover, Debt to Asset Ratio, and Return on Assets have a combined effect on Price to Book Value, as indicated by the F-value of 2.779 > F-table value of 2.67. Keywods: current ratio, total asset turnover, price to book value